AN ANALYSIS OF SPEAKING ANXIETY EXPERIENCED BY THE THIRD-YEAR STUDENTS AT SMPN 2 BAYAT OF ANAMBAS ISLAND - Suhaimi; Fadly Azhar; Eliwarti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on the study that aims to find out the levels and the major causes of speaking anxiety experienced by the third-year students at SMPN 2 Bayat of Anambas Island. Total sampling was used in this research since the pool of participants was relatively small consisting of 13 students overall. In collecting the data, students were asked to fill out a set based on a modified version of the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire developed by Horwitz et al (1986). After analyzing the data, it was found that most students experienced speaking anxiety on a moderate level. The results suggested that 4 students with a percentage of 30.77% were classified as a high level, 9 students with a percentage of 69.23% were classified as a moderate level and none of the students or 0% was classified to have a low level of anxiety. Additionally, “lack of preparation”, “afraid of being laughed at” and “afraid of being called in English classes” were the major causes of speaking anxiety that most participants agreed with. Thus, some suggestions were provided with the expectation of reducing students’ anxiety while speaking English.